Dirāsah Tadrībat Maharah Allughah Fī Kitāb Ta’lim Allughah Al’arabiyah Lilshafi Altsānī Altsānawī Liwizārah Alsyu`ūn Aldīniyah - Septia Solihati; Sadiyah Ratnasari Sagala; Husnul Khatimah (Ukazh: Journal of Arabic Studies, 2022)
The aim of this research is to know the form of exercises in the Arabic language teaching book for the second year of High school of the Indonesian Religious Ministry in 2020. This research took the descriptive-analytical approach as a method or pattern that is used to research from collecting information related to the exercises, and then identifying the types and patterns of the exercises. This research reached one conclusion, which is that the exercises in the Arabic language teaching book for the second secondary grade of the Indonesian Ministry of Religious Affairs are types, professions are exercises of Arabic language skill (reading, writing, listening, and speaking). These exercises are included in the book of teaching Arabic for the second grade of secondary school of the Indonesian Ministry of Religious Affairs in 2020. Tujuan dari penelitian ini adalah untuk mengetahui bentuk-bentuk soal latihan dalam buku ajar bahasa Arab kelas II (dua) Sekolah Menengah Atas yang diterbitkan oleh Kementerian Agama RI Tahun 2020. Penelitian ini menggunakan pendekatan deskriptif analitis sebagai metode atau pola yang digunakan untuk penelitian dari mengumpulkan informasi yang berkaitan dengan latihan, dan kemudian mengidentifikasi jenis dan pola latihan. Dari penelitian ini didapatkan satu kesimpulan, bahwa latihan-latihan dalam buku tersebut mencakup semua empat maharaat lughawiyyah (keterampilan bahasa Arab) yakni; maharah al istima’ (keterampilan menyimak), maharah al qiraah (keterampilan membaca), maharah al kalam (keterampilan berbicara) dan maharah al kitabah (keterampilan menulis). هدف هذا البحث إلى معرفة شكل التدريبات في كتاب تعليم اللغة العربية للصف الثاني الثانوي للوزارة الدينية الإندونيسية عام 2020. وهذا البحث سلك المنهج الوصفي التحليلي على أنه أسلوب أو نمط يتم استخدامه للبحث من جمع المعلومات ما يتعلق بالتدريبات، ثم تعيين أنواع التدريبات وأنماطها. ووصل هذا البحث إلى ناتجة واحدة هي أن التدريبات في كتاب تعليم اللغة العربية للصف الثاني الثانوي لوزارة الشؤون الدينية الإندونيسية أنواع، وأنماط التدريبات من مهارة اللغة العربية التي وردت في كتاب تعليم اللغة العربية للصف الثاني الثانوي لوزارة الشؤون الدينية عام 2020 هي (القراءة، والكتابة، والاستماع، والكلام)